If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -1(9x + -6) = 18 Reorder the terms: 15x + -1(-6 + 9x) = 18 15x + (-6 * -1 + 9x * -1) = 18 15x + (6 + -9x) = 18 Reorder the terms: 6 + 15x + -9x = 18 Combine like terms: 15x + -9x = 6x 6 + 6x = 18 Solving 6 + 6x = 18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 6x = 18 + -6 Combine like terms: 6 + -6 = 0 0 + 6x = 18 + -6 6x = 18 + -6 Combine like terms: 18 + -6 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| (2y+1)+(3x-6y)=2+x | | 12d^2-11dt-15t^2=0 | | -9=2(x-4) | | -9(1/2x-3)= | | 6(x^2)-x-1=0 | | (2y+1)+(3x-6)=2+x | | 6-6x=5x-9x-2x | | 8x/7-3/4=6/2-4x/4 | | 3x+-3=180 | | (2x+4)(x+4)=196+3x | | 10m+6=6m+30 | | x-15=x/77 | | -4p-12=12 | | w+2.9=6.4 | | z^2=-2z-14 | | -3/8t=1/6 | | y=20-3(1) | | g=y-cx | | 8(3n+3)=8(6n+3)+2 | | 3(1.5x+9)= | | 2(3x-2)=3(4x+5)+7X | | 144x=3268.80 | | 5x-12+x=-13 | | 4/3x3.14x3.04^3 | | -4p+8(p+3)=4(p-8)+2 | | 6(x+4)-3x=11 | | f(2.5)=2x^2-3+7 | | (4x-15)+(5x+11)+(5x+5)+(6x+19)=360 | | -6.5-4x-1.6-3x=-6+9.8 | | 7(x^2)-2=5x | | 8xt=32 | | 2(5x+4)-2(9x+2)= |